2020
DOI: 10.1093/pcp/pcaa113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DELLA Proteins by Post-translational Modifications

Abstract: DELLA proteins are the negative regulators of the gibberellin (GA) signaling pathway. GAs have a pervasive effect on plant physiology, influencing processes that span the entire life cycle of the plant. All the information encoded by GAs, either environmental or developmental in origin, is canalized through DELLAs, which modulate the activity of many transcription factors or transcriptional regulators. GAs unlock the signaling pathway by triggering DELLA polyubiquitination and degradation by the 26S proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 101 publications
0
31
0
Order By: Relevance
“…In response to shade and elevated ambient temperatures, COP1 directly targets DELLAs for degradation and thereby promotes plant growth under these conditions ( Blanco-Touriñán et al, 2020a ). DELLAs are also degraded in response to GA via the SLEEPY1 (SLY1) ubiquitin ligase ( Dill et al, 2004 ; Blanco-Touriñán et al, 2020b ). SLY1 and COP1 interact with different domains in the DELLA proteins, suggesting independent mechanisms ( Blanco-Touriñán et al, 2020a ).…”
Section: The Cop1/spa Complex In Hormonal Signalingmentioning
confidence: 99%
“…In response to shade and elevated ambient temperatures, COP1 directly targets DELLAs for degradation and thereby promotes plant growth under these conditions ( Blanco-Touriñán et al, 2020a ). DELLAs are also degraded in response to GA via the SLEEPY1 (SLY1) ubiquitin ligase ( Dill et al, 2004 ; Blanco-Touriñán et al, 2020b ). SLY1 and COP1 interact with different domains in the DELLA proteins, suggesting independent mechanisms ( Blanco-Touriñán et al, 2020a ).…”
Section: The Cop1/spa Complex In Hormonal Signalingmentioning
confidence: 99%
“…Intriguingly, the BnRGL2 gene relative expression was not observed in the drought treatment ( Figure 10). Thus, these ndings indicate the presence of unidenti ed cis-elements and signify that the expression of BnDELLAs might be regulated through posttranscriptional modi cation [42,44], which determines the antagonistic and synergistic effects of BnDELLAs in response to environmental uctuations. To further investigate the biological process associated with BnDELLA genes, we had performed the GO enrichment analysis.…”
Section: Discussionmentioning
confidence: 79%
“…The regulatory purpose of DELLAs and their interacting proteins have been characterized widely in various plant species; however, a possible underlying posttranscriptional modi cation of DELLAs in response to environmental stresses is still unclear [42][43][44]. It has been reported that miRNAs play a signi cant role in transcriptional and post-transcriptional level to modulate gene expression under stresses [45,46].…”
Section: Prediction Of the Bn-micrornas Putative Targets Sites Of Bndmentioning
confidence: 99%
“…In contrast, micrografting experiments between hypocotyls of Arabidopsis wild-type (Col-0) used as scions and GA-deficient mutant rootstocks have induced severe dwarfing and late flowering, suggesting a rootstock-mediated modulation of shoot GA endogenous concentrations [ 35 ]. Since GAs are negatively regulated by DELLA proteins [ 62 ], the ectopic expression of the gain-of-function mutant Mhgai1 encoding a DELLA protein in tomato reduced plant height [ 63 ]. A grafting experiment demonstrated the long-distance movement of Mhgai1 mRNAs and their effect on dwarfing of the scion genotype [ 64 ], as seems to occur in plants grafted onto Terrano.…”
Section: Discussionmentioning
confidence: 99%